2014
DOI: 10.1590/s0104-66322014000100002
|View full text |Cite
|
Sign up to set email alerts
|

The stimulating effects of the addition of glucose on denitrification and removal of recalcitrant organic compounds

Abstract: -A laboratory scale aerobic oxidation ditch combined with an anoxic reactor was conducted to treat wastewater from a chemical industrial park in Tianjin, China. The wastewater exhibited a low biodegradability, and the results of gas chromatography mass spectrometry (GC-MS) analysis showed that some recalcitrant organic components are present in the wastewater. Ammonia nitrogen (NH 4 + -N) removal efficiency of over 90% was obtained. However, the removal efficiencies of total nitrogen (TN) and chemical oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Glucose served as a better carbon source for active biomass, which was easily biodegradable to form acetate. Therefore, the removal percentage of COD during the first five days of feeding with glucose were lower than 70%, but from the 6 th day, as microbial growth increased, the removal efficiency increased to 80% (Figure 3), in accordance with the finding of Wang et al (2014), who found that when glucose was added to the anaerobic reactor from day 105 to day 138, the total COD removal rate was increased from 23.93% to 85.71%. In order to check the reactor efficiency, effluent COD was compared with influent COD.…”
Section: Effect Of Glucose During the Uasb Start-up Periodsupporting
confidence: 84%
“…Glucose served as a better carbon source for active biomass, which was easily biodegradable to form acetate. Therefore, the removal percentage of COD during the first five days of feeding with glucose were lower than 70%, but from the 6 th day, as microbial growth increased, the removal efficiency increased to 80% (Figure 3), in accordance with the finding of Wang et al (2014), who found that when glucose was added to the anaerobic reactor from day 105 to day 138, the total COD removal rate was increased from 23.93% to 85.71%. In order to check the reactor efficiency, effluent COD was compared with influent COD.…”
Section: Effect Of Glucose During the Uasb Start-up Periodsupporting
confidence: 84%
“…However, no significant changes were observed in the band pattern while Methanosarcina genus remained after DO addition, proving that DO did non‐significantly affect Archaea populations as it has been reported by other authors (Durán et al, 2008; Ergüder & Demirer, 2005). There are reports about toxic compounds biological elimination is carried out through cometabolic pathways were the oxygen improves the acrylates, pentachlorophenol, styrene trichlorophenol, and VA methanogenesis (Garibay‐Orijel et al, 2005; Wang et al, 2014). Besides, the 2 mg DO·L −1 addition is reported as not toxic for sludge's and the oxygen removed several toxic compounds, which were not previously eliminated under anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that glucose represent a strong supporter, because it makes microorganisms grew and induces enzymes and cofactors required for cometabolism (Li et al, 2014;Tobajas et al, 2012). In addition to the fact, since glucose is a positive effector over methanogenesis recalcitrant chemicals such as acrylates, styrene, vinyl acetate, trichlorophenol, and pentachlorophenol, it provides the greatest electron flow (Dur an et al, 2008(Dur an et al, , 2011Garibay-Orijel et al, 2006;Wang et al, 2014). However, there is not enough evidence in order to understand the carbon sources action such as glucose over the toxic compound's biological degradation through cometabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Additional carbon sources (e.g. glucose) can provide a synergistic effect, improving bacterial and fungal growth and enhancing the treatment efficiency of pulp and paper wastewater (Raj et al , 2014; Wang et al , 2014). In fact, without the assistance of co-metabolic substrates, it would take more time for microorganisms to degrade organic matter due to the inhibition of microbial function caused by the calcitrant and toxic organics presented in wastewater (Li et al , 2021).…”
Section: Resultsmentioning
confidence: 99%